2022
DOI: 10.3390/pharmaceutics15010097
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic Properties of Prodigiosin and the BH3-Mimetic Obatoclax (GX15-070) in Melanoma

Abstract: Metastasis is the primary cause of death in cancer patients. Many current chemotherapeutic agents only show cytotoxic, but not antimetastatic properties. This leads to a reduction in tumor size, but allows cancer cells to disseminate, which ultimately causes patient death. Therefore, novel anticancer compounds with both effects need to be developed. In this work, we analyze the antimetastatic properties of prodigiosin and obatoclax (GX15-070), anticancer drugs of the Prodiginines (PGs) family. We studied PGs’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…PG has shown strong anti-cancer effects, with proven efficacy in treating melanoma, breast cancer, lung cancer, lymphocytic leukemia, and glioblastoma ( Pan et al, 2012 ; Brown et al, 2015 ; Wang et al, 2016 ; Cheng et al, 2018 ; Chiu et al, 2018 ; Espona-Fiedler et al, 2022 ). It triggers apoptosis in cancer cells, including multidrug-resistant ones, with minimal toxicity to normal cells ( Elahian et al, 2013 ).…”
Section: Structures and Properties Of Prodigiosinmentioning
confidence: 99%
See 1 more Smart Citation
“…PG has shown strong anti-cancer effects, with proven efficacy in treating melanoma, breast cancer, lung cancer, lymphocytic leukemia, and glioblastoma ( Pan et al, 2012 ; Brown et al, 2015 ; Wang et al, 2016 ; Cheng et al, 2018 ; Chiu et al, 2018 ; Espona-Fiedler et al, 2022 ). It triggers apoptosis in cancer cells, including multidrug-resistant ones, with minimal toxicity to normal cells ( Elahian et al, 2013 ).…”
Section: Structures and Properties Of Prodigiosinmentioning
confidence: 99%
“…Inhibiting tumor cell migration and motility is essential for achieving anti-cancer effects. Research by Margarita Espona-Fiedler and her team found that PGs effectively reduce the adhesive capability of melanoma cells, impeding their ability to colonize distant organs and preventing metastasis ( Espona-Fiedler et al, 2022 ). PG treatment also decreases the adhesive capacity of metastatic lung cancer cells and reduces filopodia formation in melanoma cells, which are crucial for cancer cell migration and proliferation.…”
Section: Structures and Properties Of Prodigiosinmentioning
confidence: 99%
“…Surgical intervention and chemotherapy, as the most common therapeutic methods, may be associated with different complications ( Debela et al, 2021 ; Zeng et al, 2023 ). Despite the development of different therapy methods, metastatic tumors are mainly untreatable and are responsible for the preponderance of deaths due to cancer ( Espona-Fiedler et al, 2023 ). A major barrier to the development of efficient therapies is the complexity of tumors.…”
Section: Introductionmentioning
confidence: 99%